Soil Microbial Diversity and Network Organization Respond to Land Use and Agricultural Inputs Worldwide - Zaki Saati‐Santamaría; Sergio Pérez‐Gorjón; Daniel Abel‐Schaad; Alberto Acedo‐Bécares; Francisca Alba‐Sánchez; Amanda Lucia Alves; Weronika Babinska‐Wensierska; Jorge Ariel Marfetán; Carolina Barroetaveña; Kara Barry; Francisco Beitia; Katerina Biniari; et al. (Global Change Biology, 2026)
Soil microbiomes are critical for ecosystem functioning, yet the global influences of climate and agricultural practices on their diversity and structure remain incompletely characterized. Here we analyzed 1921 soil samples from 33 countries worldwide across diverse biomes to assess how climate gradients and agricultural inputs, including pesticides and fertilizers, shape prokaryotic and fungal communities. We found that microbial diversity peaks at intermediate temperatures and differs markedly between natural and agricultural soils, with agriculture increasing microbial diversity while altering community composition and ecological guilds. Pesticide use selectively reduced bacterial diversity and shifted fungal guilds, decreasing ectomycorrhizal fungi while increasing saprotrophs, whereas fertilization reduced microbial network cohesion, with organic and inorganic fertilizers eliciting distinct community responses. These findings reveal that climatic factors and agricultural management jointly influence soil microbial diversity, community structure, and network connectivity, with implications for soil health and ecosystem resilience in managed landscapes. Overall, our results demonstrate that agricultural practices, including the use of pesticides and both organic and inorganic fertilizers, act as strong ecological filters that reshape soil microbiomes worldwide—enhancing apparent diversity but driving a functional shift toward less mutualistic, more fragmented, and potentially less resilient communities.